2016
DOI: 10.1016/j.dsr.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale and sub-mesoscale variability in phytoplankton community composition in the Sargasso Sea

Abstract: The Sargasso Sea is a dynamic physical environment in which strong seasonal variability combines with forcing by mesoscale (~ 100 km) eddies. These drivers determine nutrient, light, and temperature regimes and, ultimately, the composition and productivity of the phytoplankton community. On four cruises (2011 and 2012; one eddy per cruise), we investigated links between water column structure and phytoplankton community composition in the Sargasso at a range of time and space scales. On all cruises, cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 73 publications
(127 reference statements)
1
25
0
Order By: Relevance
“…Our objective here was to focus on the cyanobacteria community and their cell and carbon export during the winter and summer cruises of 2012. Cotti‐Rausch et al () and De Martini () showed that seasonality was the main driver of the phytoplankton community composition during our study, even though some variability could be observed in response to the mesoscale eddies. Detailed information on hydrography, nutrients and phytoplankton composition at each station can be found in Cotti‐Rausch et al () and De Martini ().…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Our objective here was to focus on the cyanobacteria community and their cell and carbon export during the winter and summer cruises of 2012. Cotti‐Rausch et al () and De Martini () showed that seasonality was the main driver of the phytoplankton community composition during our study, even though some variability could be observed in response to the mesoscale eddies. Detailed information on hydrography, nutrients and phytoplankton composition at each station can be found in Cotti‐Rausch et al () and De Martini ().…”
Section: Resultsmentioning
confidence: 48%
“…This study is part of the Trophic‐BATS project, which investigated the plankton community in the Sargasso Sea, their trophic dynamics and relationship with carbon export in 2011 and 2012 (Cotti‐Rausch et al ; De Martini ). Our objective here was to focus on the cyanobacteria community and their cell and carbon export during the winter and summer cruises of 2012.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of sAC and ssAC2, similar or lower microplankton fraction values were found in comparison with those in the CZ during the first weeks of tracking. For sAC, this could be explained as a response to the physical dynamics of this eddy type, usually characterized by a downward displacement of isopycnals, which forces a flush of nutrients below the euphotic zone and the consequent decrease in primary production [3,[9][10][11]. In the case of ssAC2, Morales et al [33] have previously described that this eddy was interacting with a coastal front during a relaxation phase of upwelling, time at which the nanoplankton made the largest contributions to total Chl-a.…”
Section: Shifts On Phytoplankton Size Classes Within Mesoscale Eddiesmentioning
confidence: 99%
“…In the case of mesoscale structures (10-100 km, day-months), such as fronts and eddies, their movement through the ocean causes modifications in the physical properties (i.e., light, temperature) of the water column, changing nutrient conditions and, consequently, the phytoplankton community structure [3][4][5]. Mesoscale eddies occupy 25-30% of the surface ocean, contain more than 80% of the kinetic energy of oceanic circulation, and can generate different biological responses depending on eddy type (i.e., surface cyclonic/anticyclonic or subsurface anticyclonic eddy) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Observations have shown that phytoplankton biomass and community structure have characteristic temporal and spatial scales corresponding most closely with the oceanic mesoscale and submesoscale (Platt, 1972;Strass, 1992;Abbott and Letelier, 1998;Doney et al, 2003;Cotti-Rausch et al, 2016). However, most global ocean models incorporating biogeochemical and ecological processes (especially those coupled in climate studies) do not resolve scales less than ∼ 1 • .…”
Section: Introductionmentioning
confidence: 99%